Investigation of the effect of sea waves on coastal ecosystem - (:unkn) unknown (My University, 2013)
An experimental study was carried out to determine the effects of waves on coastal life. Wave dynamism occurs as a result of beach porosity. Oxygen change at water levels was studied along the coast. Beyond the enlargement of oxygenated sediment surface, the increased habitat complexity itself often leads to a higher diversity of benthic communities. The beach was built as a natural sandy beach at laboratory scale. Waves infiltrate through the groundwater which leads to an increase of dissolved oxygen (DO) concentration in water. Beach profiles were analyzed to obtain the area of erosion and offshore bar, center of gravity of offshore bar, and wave run-up height. Seven vertical lines were determined, and DO concentration and profile data were collected for each line. Regular waves were used during the experiments. Beach sand with a mean diameter of 0.3 mm was selected for the study, and the slope of the beach was 1:5. The data in flume showed that DO concentration did not change under the places where there were stable measurement points, and at the region that runup/rundown swash flows did not reach. Harmonic oscillations of DO concentration were observed more in places close to water surface than those close to sediment surface. © by PSP.
Keywords: Beach; Coastal life; Dissolved oxygen